2017
DOI: 10.1038/tp.2017.165
|View full text |Cite|
|
Sign up to set email alerts
|

Abolishing Tau cleavage by caspases at Aspartate421 causes memory/synaptic plasticity deficits and pre-pathological Tau alterations

Abstract: TAU mutations are genetically linked to fronto-temporal dementia (FTD) and hyper-phosphorylated aggregates of Tau form neurofibrillary tangles (NFTs) that constitute a pathological hallmark of Alzheimer disease (AD) and FTD. These observations indicate that Tau has a pivotal role in the pathogenesis of neurodegenerative disorders. Tau is cleaved by caspases at Aspartate 421 , to form a Tau metabolite known as δTau; δTau is increased in AD, due to the hyper-activation of caspases in AD brains. δTau is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…At any rate, of the evidence that our mouse model reproduced some of the phenotypes already reported 39 , 42 44 supports a role of tau in learning, memory and synaptic plasticity. Moreover, recent data showing that caspase cleavage of tau at Asp 421 is essential for normal memory and normal LTP 59 further underline this important role of tau. In future studies it will be important to further test the role of tau in cognition and synaptic plasticity –for example to determine how early LTP is compromised by tau deletion- and to determine whether the effect of ablating tau expression is similar in both sexes.…”
Section: Discussionmentioning
confidence: 93%
“…At any rate, of the evidence that our mouse model reproduced some of the phenotypes already reported 39 , 42 44 supports a role of tau in learning, memory and synaptic plasticity. Moreover, recent data showing that caspase cleavage of tau at Asp 421 is essential for normal memory and normal LTP 59 further underline this important role of tau. In future studies it will be important to further test the role of tau in cognition and synaptic plasticity –for example to determine how early LTP is compromised by tau deletion- and to determine whether the effect of ablating tau expression is similar in both sexes.…”
Section: Discussionmentioning
confidence: 93%
“…[45][46][47][48] ). Mice expressing endogenous Tau non-cleavable at D421 unexpectedly show Tau hyperphosphorylation, memory impairment, and synaptic plasticity deficits, indicating that TauΔD421 could be beneficial in this model or that the D421N mutation altered Tau function 32 . However, our work contradicts studies implicating TauΔD402/D421 in Tau aggregation and toxicity in AD brains [7][8][9][10][11][12][13] , transgenic animal models [24][25][26][27][28][29]31,49 , neuronal cells [17][18][19][20][21][22] , and recombinant proteins 7,23 .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, TauC3 and TAU62 mice show memory impairments and synaptic alterations 28,29 . In contrast, transgenic mice expressing uncleavable D421 endogenous murine Tau exhibit long-term potentiation and cognitive deficits 32 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that while the truncation of full-length tau at D421 translated into a distinct distribution of tau variant in the axonal terminal, the functional benefit towards the phospho-mimicking E14. In supporting this, a study found that the knock-in mutant with an abolished D421 cleavage site of mouse tau showed memory/synaptic plasticity defects 67 . Together with our result, it raises a possibility that, during the pathogenesis of tauopathy, if the hyperphosphorylated tau can be truncated at D421 at an earlier time point, it may reduce tau-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 92%